Antidepressants promote the spread of antibiotic resistance via horizontally conjugative gene transfer. (25th August 2022) - Ding, Pengbo; Lu, Ji; Wang, Yue; Schembri, Mark A.; Guo, Jianhua
Abstract: Antibiotic resistance is a global concern threatening public health. Horizontal gene transfer (HGT) between bacterial species contributes greatly to the dissemination of antibiotic resistance. Conjugation is one of the major HGT pathways responsible for the spread of antibiotic resistance genes (ARGs). Antidepressant drugs are commonly prescribed antipsychotics for major depressive disorders and are frequently detected in aquatic environments. However, little is known about how antidepressants stress bacteria and whether such effect can promote conjugation. Here, we report that commonly prescribed antidepressants, sertraline, duloxetine, fluoxetine, and bupropion, can promote the conjugative transfer of plasmid‐borne multidrug resistance genes carried by environmentally and clinically relevant plasmids. Noteworthy, the transfer of plasmids across bacterial genera is significantly enhanced by antidepressants at clinically relevant concentrations. We also reveal the underlying mechanisms of enhanced conjugative transfer by employing flow cytometric analysis, genome‐wide RNA sequencing and proteomic analysis. Antidepressants induce the production of reactive oxygen species and the SOS response, increase cell membrane permeability, and upregulate the expression of conjugation relevant genes. Given the contribution of HGT in the dissemination of ARGs, our findings highlight the importance of prudent prescription of antidepressants and to the potential connection between antidepressants and increasing antibiotic resistance.